Reka Cipta Aplikasi Berbasis Mobile "Paradise of Central Tapanuli" sebagai Pusat Informasi Wisata Bahari di Tapanuli Tengah - Situmeang, Rizky Akbar; Sandrina, Tata Kindy; Simpa, Zevi Yarti; Alda, Muhammad (MODELING: Jurnal Program Studi PGMI, 2023)
Central Tapanuli is a regency in North Sumatra which is located on the west coast. This district has several interesting tourist attractions that can be visited such as Kalimantung Island, Mursala Island, Putri Island, Coral Island, and Bakar Island. However, due to the lack of information and promotions that have been carried out, many people do not know how many interesting islands there are in Central Tapanuli. Therefore, a tool is needed to promote these tourist attractions so as to increase the tourism sector in the area. For this reason, an application called "Paradise of Central Tapanuli" was made, where this application introduced tourism in Central Tapanuli. The method used is descriptive method. Descriptive method is a method in examining the status of a human group, an object, a condition or a thought or class of tourism in the present. . This application was built using the Kodular website which is a website application that allows users to create applications based on the Android operating system using Block Programming so that users do not need to do coding (writing programming code). This application is expected to help tourists who want to get information about tourism in Central Tapanuli Province quickly and precisely.